Microfluidic 3D cell culture: potential application of collagen hydrogels with an optimal dose of bioactive glasses - Faezeh Ghobadi; Maryam Saadatmand; Sara Simorgh; Peiman Brouki Milan (Scientific Reports)
Abstract We engineered a microfluidic platform to study the effects of bioactive glass nanoparticles (BGNs) on cell viability under static culture. We incorporated different concentrations of BGNs (1%, 2%, and 3% w/v) in collagen hydrogel (with a concentration of 3.0 mg/mL). The microfluidic chip’s dimensions were optimized through fluid flow and mass transfer simulations. Collagen type I extracted from rat tail tendons was used as the main material, and BGNs synthesized by the sol–gel method were used to enhance the mechanical properties of the hydrogel. The extracted collagen was characterized using FTIR and SDS-PAGE, and BGNs were analyzed using XRD, FTIR, DLS, and FE-SEM/EDX. The structure of the collagen-BGNs hydrogels was examined using SEM, and their mechanical properties were determined using rheological analysis. The cytotoxicity of BGNs was assessed using the MTT assay, and the viability of fibroblast (L929) cells encapsulated in the collagen-BGNs hydrogel inside the microfluidic device was assessed using a live/dead assay. Based on all these test results, the L929 cells showed high cell viability in vitro and promising microenvironment mimicry in a microfluidic device. Collagen3-BGNs3 (Collagen 3 mg/mL + BGNs 3% (w/v)) was chosen as the most suitable sample for further research on a microfluidic platform.